The Relationship between Job Satisfaction, Organizational Commitment, and Turnover Intention of Doctoral Lecturers: A Case Study of Universities in Mianyang, China - Jing, Zaiping; Photchanachan, Sarana (Nimitmai Review Journal, 2021)
This article aimed to investigate the relationship between organizational commitment and job satisfaction towards doctoral lecturers’ turnover intention in Mianyang, China. From the target population of 904 doctoral lecturers who has been working in 9 universities in Mianyang, China, there were 302 samples selected by adopting purposive sampling method according to Yamane’s Equation Formula. The instrument for collecting data was a questionnaire. This study was a quantitative research by using survey. The main tools of analysis were frequency, percent and linear regression analysis to test variables and to test hypothesis. All tests were based on 0.05 level of significance. From the analysis results, Doctoral lecturers’ job satisfaction, organizational commitment had negative relationship on turnover intention. There was significant relationship between doctoral lecturers’ job satisfaction, organizational commitment and turnover intention. Therefore, it also recommended among others that governments, society, and universities should pay more attention to doctoral lecturers’ job satisfaction, effectively prevent them from forming a turnover intention, and stabilize them as a team.